Alberta First Nations Consultation & Accommodation Handbook - Laidlaw, David; Passelac-Ross, Monique (Canadian Institute of Resources Law, 2014)
We would like to thank the Alberta Law Foundation for their generous support in the development of this occasional paper for this project. We would also like to thank the attendees at the Focus Group on January 28, 2013 and the participants at the First Nations Round Table on Aboriginal Consultation and Accommodation on November 18, 2013 for their thoughtful comments. To our colleagues at CIRL and the Faculty of Law at the University of Calgary, your unending support and stimulating discussion is appreciated. Alberta has had two attempts to develop a First Nation’s consultation and accommodation process. The first in 2005 was controversial for First Nations and frustrating for resource companies. The First Nation Consultation Policy (2013) was released on August 16, 2013. There were some conceptual improvements such as the centralization of First Nation Consultation and a consultation levy on resource companies. There are notable failures including the process of developing the new policy and the continued misunderstanding of the governing Treaties. Aboriginal consultation in Alberta after the new Policy will still be a frustrating, complicated, and expensive exercise despite government, industry, First Nations’ and public hopes. It need not be so. In this report, this latest attempt is described and critiqued with best practices from other jurisdiction suggested to correct the flaws. No Alberta Law Foundation;